PENERAPAN MODEL PEMBELAJARAN STUDENT FACILITATOR AND EXPLAINING UNTUK MENINGKATKAN HASIL BELAJAR AFEKTIF SISWA DALAM PEMBELAJARAN FISIKA KELAS XI SMAN PLUS PROVINSI RIAU - Fathurrahmah Fathurrahmah; Hendar Sudrajat; Nur Islami (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This research aimed to see the improve of the student affective learning result of class XI SMAN Plus Riau Province by applying the student facilitator explaining learning model on Wafe Classification Lesson. The subjects of this research was 25 students of class XI MS 1 SMAN Plus Riau Province 2016/2017 academic year. The data in this research was primary data that obtained from pretest and posttest score using self-assessment, peer assessment and observation assessment sheets that was analyzed descriptively. Questionnaire of self-assessment and peer assessment consists of seven indicators that is honest, good manners, confidence, responsibility, tolerance, curiosity and hard work. The observation sheets consists of five indicators: responsibility, trust, tolerance, curiosity and hard work. The result of affective learning in this research shows the increasing of self-assessment, that is 0.10 with low category, peer assessment 0.10 with low category and the observation is 0.38 with medium category. At can be concluded from all assessments with existing indicators obtained a gain score that is 0.19 with low category.Keywords: Affective learning, Student facilitator and Explaning and Wave Classification